Influence of personality factors on job satisfaction among secondary school counsellors in Selangor - Jaapar, Jafny; Wan Jaafar, Wan Marzuki (Malaysia Association of Research and Education for Educators, 2017)
This research is designed to identify school counsellors’ personality factors and to determine whether these factors determine the counsellors’ work satisfaction. Furthermore, the research is also designed to gauge the counsellors’ level of work satisfaction. 310 secondary school counsellors from 10 different districts in the state of Selangor were randomly selected as respondents. The research uses the quantitative approach. Data is obtained through a translated questionnaire taken from BFI and JDI. The reliability factor of the instrument is between 0.73 to 0.80. 142 counsellors (45.8%) of the respondents recorded a high degree of job satisfaction; 143 (46.1%) recorded average satisfaction while 25 (8.1%) respondents stated a low level of satisfaction. The results of the research also indicate that, with reference to the relationship between personality factor and job satisfaction, two out of five personality factors (namely agreeableness and neuroticism) show significant relationship with job satisfaction. All relationships show a positive correlation except for the relationship between agreeableness and neuroticism factors and job satisfaction. The results also indicate a significant influence of personality factor towards the counsellors’ job satisfaction. The implication of the study is also discussed and proposed in this article.